Implementasi Penggunaan Software Accurate Online di Perumda Percada - Bela Triyani; Febriana Tri Syafa’ati; Meli Anggraeni; Elvia Ivada (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
This writing aims to determine the implementation of the use of Accurate online software at the Sukoharjo Regional Public Printing and Publishing Company (Perumda Percada). The main objective is to determine the positive impact of using Accurate online software on Perumda Percada. Perumda Percada as an entity operating in the printing industry, this company is faced with challenges in managing inventory, financial monitoring and efficient resource management. Information data is obtained from direct observation. The results show that the implementation or application of Accurate online has helped in recording finances at Perumda Percada. User-friendly, Accurate online makes it easier for employees to input and collaborate between departments. Apart from that, Accurate online software also helps management in monitoring the financial reports that have been produced.